Problem based learning for preclinical undergraduate medical studies at Chitwan Medical College - Timilsina, Sameer; Karki , Sirisa (Journal of Chitwan Medical College, 2024)
The introduction of problem based learning (PBL) in contemporary medical education has enabled learners to emphasize their learning behaviour fostering self-directed learning, critical thinking, communication skills, and application of knowledge in real life scenarios. Abiding by the parent curriculum, some parts of teaching-learning activity at Chitwan Medical College are conducted using PBL. It is conducted at the start of human body systems and concluded with a seminar. The objectives to be covered during PBL sessions are collected from each department and pertinent clinical conditions is decided by all faculties from basic science subjects including community medicine department whenever relevant.